ANALISIS PERSEDIAAN BARANG MENGGUNAKAN METODE FEFO PADA BAGIAN PERLENGKAPAN STMIK PROFESIONAL - Kurnia Yahya (PROGRESS, 2018)
This study analyzes the ideal inventory system so that it can help manage a company in the decision-making process. Determination of the amount of inventory aims to rank groupings of goods that are often used and usually of a small amount but have a large investment cost. The management sued required to control the amount of effective inventory so that goods are available in sufficient quantities, not too much and not too little. A large inventory of goods will cause storage costs too high and allow goods damaged, but if the inventory is little feared it will run out and affect the smooth running of daily activities. Therefore, it is necessary to control available goods. The process carried out to get the amount of inventory based on priority is to use the FEFO (First Expire First Out) method. Inventory based goods by using the FEFO method is a recommendation for management to decide the amount of inventory based on their interests. The results obtained are implementing a system that can streamline the amount of inventory agree their usage needs.